Intraoperative detection of colorectal and pancreatic liver metastases using SGM-101, a fluorescent antibody targeting CEA. (March 2021) - Meijer, Ruben P.J.; de Valk, Kim S.; Deken, Marion M.; Boogerd, Leonora S.F.; Hoogstins, Charlotte E.S.; Bhairosingh, Shadhvi S.; Swijnenburg, Rutger-Jan; Bonsing, Bert A.; Framery, Bérénice; Fariña Sarasqueta, Arantza; Putter, Hein; Hilling, Denise E.; et al.
Abstract: Background: Fluorescence-guided surgery can provide surgeons with an imaging tool for real-time intraoperative tumor detection. SGM-101, an anti-CEA antibody labelled with a fluorescent dye, is a tumor-specific imaging agent that can aid in improving detection and complete resection for CEA-positive tumors. In this study, the performance of SGM-101 for the detection of colorectal and pancreatic liver metastases was investigated. Methods: In this open-label, non-randomized, single-arm pilot study, patients were included with liver metastases from colorectal origin and intraoperatively detected liver metastases from pancreatic origin (during planned pancreatic surgery). SGM-101 was administered two to four days before the scheduled surgery as a single intravenous injection. Intraoperative fluorescence imaging was performed using the Quest Spectrum® imaging system. The performance of SGM-101 was assessed by measuring the intraoperative fluorescence signal and comparing this to histopathology. Results: A total of 19 lesions were found in 11 patients, which were all suspected as malignant in white light and subsequent fluorescence inspection. Seventeen lesions were malignant with a mean tumor-to-background ratio of 1.7. The remaining two lesions were false-positives as proven by histology. Conclusion: CEA-targeted fluorescence-guided intraoperative tumor detection with SGM-101 is feasible for the detection of colorectal and pancreatic liver metastases.